Edukasi Pencegahan Enam Perilaku Berisiko untuk Meningkatkan Kesadaran Remaja di SMP Negeri 4 Amarasi Selatan - Elisabeth Novantri Goo; Marleni S. Banamtuan; Fransiskus J.A. Mole; Georgius N. Mura (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Adolescents are particularly vulnerable to risky behaviors that may adversely affect their physical, psychological, and social development. Preliminary observations at SMP Negeri 4 Amarasi Selatan, Retraen Village, identified students' vulnerability to bullying, early smoking experimentation, unhealthy dating, and irresponsible internet use, indicating the need for preventive educational interventions. This community service program aimed to enhance students' understanding of six adolescent risky behaviors, namely unhealthy dating, smoking, drug abuse, bullying, gender inequality, and negative internet use. The program was conducted in April 2026 involving 70 students using a participatory approach through interactive lectures, group discussions, educational videos, and role-play. Evaluation was carried out through observation, question-and-answer sessions, and reflective discussions. The evaluation indicated that students were able to identify various forms of risky behavior, explain their impacts, and propose appropriate prevention strategies in situations commonly encountered in daily life. The educational materials and learning media developed through this program can support school-based counseling services and character education as part of sustainable preventive efforts.